Optimizing metal/n-AlGaN contact by recessed AlGaN heterostructure with a polarization effect. Issue 9 (14th April 2023) - Chen, Yuxuan; Jiang, Ke; Sun, Xiaojuan; Zhang, Zi-Hui; Zhang, Shanli; Ben, Jianwei; Wang, Bingxiang; Guo, Long; Li, Dabing
Abstract : A convenient and stable strategy is proposed to optimize the contact characteristics of metal/n-AlGaN by introducing a heterostructure with a polarization effect and etching a recess structure through the heterostructure beneath the contact metal. Abstract : With increasing Al mole fraction, n-contact has become an important issue limiting the development of Al-rich AlGaN-based devices. In this work, we have proposed an alternative strategy to optimize the metal/n-AlGaN contact by introducing a heterostructure with a polarization effect and by etching a recess structure through the heterostructure beneath the n-contact metal. Experimentally, we inserted an n-Al0.6 Ga0.4 N layer into an Al0.5 Ga0.5 N p–n diode on the n-Al0.5 Ga0.5 N layer to form a heterostructure, where a high interface electron concentration of 6 × 10 18 cm −3 was achieved with the aid of a polarization effect. As a result, a quasi-vertical Al0.5 Ga0.5 N p–n diode with a ∼1 V reduced forward voltage was demonstrated. Numerical calculations verified that the increased electron concentration beneath the n-metal induced by the polarization effect and recess structure was the main reason for the reduced forward voltage. This strategy could simultaneously decrease the Schottky barrier height as well as provide a better carrier transport channel, enhancing both the thermionic emission and tunneling processes. This investigation provides an alternative approach to obtain a good n-contact, especially for Al-rich AlGaN-based devices, such as diodes and LEDs.